Self-compassion as a predictor of body image in middle adulthood women - Rabbani, Intan Naqiya; Farisandy, Ellyana Dwi (University of Muhammadiyah Malang, 2025)
Women in middle adulthood will face changes in physical appearance. For some women, these changes can lead to negative perceptions towards their body, resulting in psychological issues. Self-compassion is known to be a protective factor against these negative perceptions. Therefore, this study aims to determine whether self-compassion predict body image in middle adulthood women. The participants in this study are 352 middle adulthood women. The measurement tools used were the Skala Welas Diri (SWD) and the Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS). This quantitative research used convenience sampling as sampling technique and simple linear regression is utilized as a data processing technique to test hypotheses. The results found that self-compassion was proven to predict body image in middle adulthood women, accounting for 17.3%. The regression test results showed R²=0.173, F(1, 350)=72.969, p<0.001. This means that the higher the self-compassion, the more positive the body image in middle adulthood women.